Stories of Power - Uncovering Dynamics of the Big Break in 21st Century Literary Production - Klempel, Annika (Satura, 2022)
In a world of transparency and unlimited access to information, it is irritating that the key to becoming a literary author still seems like an unfathomable riddle, a mythical process almost, refusing to adapt to modern-day rules. YouTube sports hundreds of videos on how to become a writer and how to publish a manuscript at a traditional publishing house. Semi-professionals and professionals try to provide knowledge to increase the “slim and uncertain” chance of a ‘big break’ in the literary market to the oversupply of creative laborers (Fürst 53-54).